2022
DOI: 10.1049/hve2.12201
|View full text |Cite
|
Sign up to set email alerts
|

Dry reforming of methane by microsecond pulsed dielectric barrier discharge plasma: Optimizing the reactor structures

Abstract: Dry reforming of CH 4 process can convert greenhouse gases into high-value-added fuels and chemicals with its broad application prospects in environmental protection and renewable energy. Non-thermal plasma is considered an effective alternative method because it can activate CH 4 and CO 2 under low temperature and atmospheric pressure. This paper is aimed to optimize the plasma-assisted dry reforming of CH 4 process in a unipolar microsecond pulsed coaxial dielectric barrier discharge by investigating the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 53 publications
(112 reference statements)
0
21
0
Order By: Relevance
“…Pulsed dielectric barrier discharge is a common plasma reactor used in plasma-enabled energy conversion. Zhang et al 9 achieved a CH 4 conversion of 27.9% by applying microsecond-pulsed DBD plasma on DRM and optimizing the reactor structures at a CH 4 : CO 2 ratio of 1 : 1 and a total flow rate of 50 ml min −1 . Zhang et al 10 and Chen et al 11 reported that NRP DBD plasma can implement non-oxidative methane conversion.…”
Section: Plasma-enabled Energy Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulsed dielectric barrier discharge is a common plasma reactor used in plasma-enabled energy conversion. Zhang et al 9 achieved a CH 4 conversion of 27.9% by applying microsecond-pulsed DBD plasma on DRM and optimizing the reactor structures at a CH 4 : CO 2 ratio of 1 : 1 and a total flow rate of 50 ml min −1 . Zhang et al 10 and Chen et al 11 reported that NRP DBD plasma can implement non-oxidative methane conversion.…”
Section: Plasma-enabled Energy Conversionmentioning
confidence: 99%
“…Pulsed dielectric barrier discharge is a common plasma reactor used in plasma-enabled energy conversion. Zhang et al 9 achieved a CH 4 conversion of 27.9% by applying microsecond-pulsed DBD plasma on DRM and optimizing the reactor structures at a CH 4 : CO 2 ratio of 1 : 1 and a total ow rate of 50 ml min −1 . Zhang et al 10 12 presented that the maximum conversion rate of methane and energy efficiency of pulsed spark plasma that can be achieved is 91.2% and 44.3% at a gas ow rate of 50 ml min −1 , respectively.…”
Section: Ntp (Plasma Only) Technologymentioning
confidence: 99%
“…Plasma species, such as electrons, atoms, ions, and radicals, enable diverse chemical reactions at room temperature and ambient pressure conditions. The type of plasma discharge, applied voltage waveforms, operational parameters of the power supply (i.e., applied voltage, frequency, and power input), reactor design, , reactant composition, gas flow rates, reactant gas ratios, and other parameters affect the synthesis process outcomes . Different discharges driven by diverse power sources such as the radio frequency, microwave, dielectric barrier discharge (DBD, alternate current, AC), , and DBD (direct current, DC) , can be used for ammonia synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] So far, numerous studies have been carried out on CH 4 to hydrogen, syngas, and hydrocarbons by NTPs. [ 17 ] For instance, Hu et al explored the interaction between plasma and catalyst in NTP‐assisted conversion of CH 4 , demonstrating that the better CH 4 conversion and the coke resistance were achieved over Pd/CeO 2 catalyst, obtaining a considerable H 2 selectivity of 50%. [ 18 ] Andersen et al researched plasma‐catalytic dry reforming of CH 4 , he found that the catalysts (Ag, Pt, and Cu) packing achieved a higher selectivity of syngas with the constant reactant conversion.…”
Section: Introductionmentioning
confidence: 99%